Temporality, vulnerability, and energy justice in household low carbon innovations. (May 2019) - Sovacool, Benjamin K.; Lipson, Matthew M.; Chard, Rose
Abstract: Decarbonisation and innovation will change the affordability of different domestic energy services. This has the potential to alleviate vulnerability to fuel poverty, but it could create new injustices unless the risks are preempted and actively mitigated. In this paper, we ask: In what ways can emerging low-carbon innovations at the household scale complement, and complicate, achieving energy justice objectives? Drawing from four empirical case studies in the United Kingdom, the paper highlights different risks that come from different types of innovation required to tackle different decarbonisation challenges. More specifically, it assesses four particular household innovations—energy service contracts, electric vehicles, solar photovoltaic (PV) panels, and low carbon heating—selected for their fit with a typology of incremental vs. radical technology and modest vs. substantial changes in user practices. It shows how in each case, such innovations come with a collection of opportunities but also threats. In doing so, the paper seeks to unveil the "political economy" of low-carbon innovations, identifying particular tensions alongside who wins and who loses, as well as the scope and temporality of those consequences. Highlights: Examines energy justice implications of low-carbon innovations in the United Kingdom. Assesses energy service contracts, electric vehicles, solar PV, and low carbon heating. Shows how innovations come with a collection of justice opportunities but also risks.